A real option model for geothermal heating investment decision making: Considering carbon trading and resource taxes. (15th December 2019) - Yu, Shiwei; Li, Zhenxi; Wei, Yi-Ming; Liu, Lancui
Abstract: By considering carbon trading and resource tax, this study established a bidimensional binominal lattice of a compound real option pricing model to help investors make decisions for geothermal heating projects. Two types of real options, to defer and to abandon, are simultaneously considered. Further, a case study on the decision making for a geothermal heating project in the Xiongan New Area in China was conducted to verify the feasibility of the proposed model. The results show that 1) the investors should delay the "invest-decision" at least one year under the real option rule but that investment value would at least 0.9 times more than that by the net present value method; 2) different subsidies methods could influence the investment time and project value, and one-time subsidies may lead to larger project value but delay the investment time; 3) The project value could be increased by conducting carbon trading but could be reduced by resource tax implementation; and 4) the value of option to defer is negatively sensitive to the initial fossil fuel price, but the value of the option to abandon is positively sensitive to the volatility of carbon price. Highlights: A bidimensional binominal lattice based real option model is proposed. Option to defer and option to abandon are simultaneously considered. Carbon trading conduct can increase project value but resource tax reduces. One-time subsidies may add project value but delay the investment time. Value of option to defer is negatively sensitive to initial fossil fuel price.